Catalytic asymmetric nucleophilic fluorination using BF3·Et2O as fluorine source and activating reagent - Weiwei Zhu (Nature Portfolio, 2021)
Catalytic asymmetric fluorination remains elusive, especially the longstanding stereochemical challenges which exist in BF3Et2O-based fluorinations. Here the authors show a catalytic asymmetric nucleophilic fluorination using BF3·Et2O as the fluorine reagent in the presence of chiral iodine catalyst.